HUBUNGAN TINGKAT KECEMASAN (ANSIETAS) DALAM MENGHADAPI OBJECTIVE STRUCTURED CLINICAL EXAMINATION (OSCE) DENGAN KUALITAS TIDUR PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - DWI NURUL RAHMADANI; DEBBY MIRANI (LP2MTBM MAKARIOZ, 2021)
According to the World Health Organization (WHO), anxiety is a mental disorder that has become a serious problem aroundthe world. Based on the 2018 Riskesdas data, mental emotional disorders which are shown by symptoms of anxiety for ages15 and over reach around 9.8% of the total population of Indonesia. This study aims to find the relationship between anxietylevels in dealing with Objective Structured Clinical Examination (OSCE) with sleep quality among FK UMSU students. Usinga descriptive analytic method with aapproach cross sectional, a sample of 146 people from FK UMSU students class 2017and 2018. Data were analyzed using Chi square. The results of thetest Chi Square showed avalue significant between thelevel of anxiety in dealing with Objective Structured Clinical Examination (OSCE) and the quality of sleep in students of theFaculty of Medicine, Muhammadiyah University of North Sumatra with p value = 0.003 (P <0.05). There is a relationshipbetween the level of anxiety in dealing with Objective Structured Clinical Examination (OSCE) and the quality of sleep instudents.